Application of a Frequency Converter in Electric Automatic Control of Central Heating. (28th June 2022) - Yin, Jingwen; Zhang, Guifeng
Abstract : In order to improve the efficiency of a central heating system's control system, this paper puts forward the application scheme of a frequency converter in central heating electrical automation control. In the central heating electrical automation control system, the frequency converter plays an important role. It can regulate and control the relevant equipment, realize the electrical automation of the heating system under the action of the frequency converter AC motor, and effectively adjust the performance and speed, so as to achieve the purpose of energy saving. The experimental results show that the temperature control strategy using a frequency converter automatic compensation method reduces the energy waste caused by manual regulation to a certain extent. When the speed of a water pump motor decreases to 4/5 of the original, the power consumption will decrease to about 52% of the original and save about 48% of the power; When the speed drops by 3/5, the power consumption is about 22% of the original, saving about 78% of the power. Conclusion . This technology can fully realize the demand of electrical automatic control of the heating system, greatly improve the stability and safety of the heating system, have good energy-saving effect, and greatly save energy consumption. The frequency converter has a remarkable effect in ensuring heating quality and improving heating efficiency in the heating industry.